Risk-taking behaviours among younger adolescents in rural and regional New South Wales: preventing adverse health outcomes. Issue 2 (4th May 2017) - Holmes, Jessica; Rawsthorne, Margot; Paxton, Karen; Luscombe, Georgina; Hawke, Catherine; Ivers, Rebecca; Skinner, Rachel; Steinbeck, Katharine
Abstract : Risk-taking behaviours during adolescence have negative short- and long-term health impacts. Maximizing the progress made through child health improvements and preventing the onset of adult ill-health require a much greater focus on health during adolescence. Understanding the biological and social factors that shape both risk and protective factors during adolescence provides the basis for effective prevention strategies. Effective prevention strategies require localized, disaggregated data to respond to heterogeneous life experiences. This paper reports on self-reported risk-taking behaviours among young adolescents growing up in rural communities in New South Wales, Australia. Quantitative analysis was undertaken to explore the relationship between risk-taking behaviour and key social determinants of health, including age, gender, cultural background and socio-economic status. It concludes that cross-cutting early intervention and prevention involving social work, youth work, education and health which builds young people's resilience is likely to assist in the development of health-protective behaviours.